PERBEDAAN PENGARUH PEMBERIAN DOSIS KAFEIN TERHADAP HOCKEY SKILL PERFORMANCE PADA ATLET HOKI SAAT KONDISI LELAH - Abdurahman Bakti, - (2022)
This study aims to determine the difference in the effect of caffeine dosage on hockey skill performance in hockey athletes when they are tired. The experimental method with a repeated measure design was carried out on 10 male athletes of UKM Hockey UPI. The instrument used to measure hockey skill performance consists of two, namely the Hockey Slalom Sprint Dribble Test and the Chapman Ball Handling Test. Treatments in the form of low-dose caffeine, high-dose and placebo and hockey training were given to the sample. To find out the significant differences between groups, one-way ANOVA analysis and Post Hoc test were used. The results showed that there were significant differences in the effect of low dose caffeine (50 mg), high dose (200 mg), and placebo on hockey skill performance in hockey athletes when they were tired. It can be concluded that the three treatments had different effects, but a low dose (50 mg) of caffeine with a placebo could be stated to have a similar effect. In addition, high doses (200 mg) of caffeine have a better effect than low doses (50 mg) of caffeine and placebo on hockey skill performance in hockey athletes when they are tired.